Design of an Electronic Voting Machine to Ensure Proper Voting Process, Minimizing Rigging, Using Radio Frequency Identification Technology - Dogra, Sudip; Bhattacharjee, Pratik; Chatterjee, Suman (International Journal of Computer Sciences and Engineering, 2025)
Electoral fraud is one of the biggest threats to democracy in India. As a solution to this problem we have proposed a modified Electronic Voting Machine which can help in reducing electoral fraud in India to a large extent. The system utilizes RFID technology to scan voter ID cards and prevent any invalid voter from casting a vote and also register only a single vote per voter. The voter ID card is also read at an electronically controlled gate, which will also have an RFID reader installed in it. It will scan the voter card and prevent any ineligible voter from entering the booth.